ANALISIS GAYA BELAJAR MATEMATIKA PADA SISWA KELAS VII SMP NEGERI OEBAKI - Abi, Alfonsa Maria (Pendidikan Matematika UNIMOR, 2020)
The reason of getting low mark in mathematics is due to the lack of students’ interest and attention. Many students feel that mathematics is hard to be learnt and to be understood as well as there is unwillingness effort to review every lesson at home along with teachers’ unawareness of students’ learning style. One of the characteristics in learning style that related to absorption, preparation and delivery of information is the students’ learning style. Learning style forms the important modality in study. The information about characteristic of students’ learning style is very important for teachers to increase the quality of learning itself and students will be easier to motivate themselves in learning as well. The aim of this research is to know the learning style of seventh grade students in SMP N Oebaki in the academic year 2017/2018.The method of this research is descriptive qualitative method and the research instrument that used are questionnaires, interview and observation. The result of this study shows that the students have visual, auditory, and kinesthetic learning style, and the dominant learning style of the students is kinesthetic learning style. Key words: Mathematical learning style, visual, auditory, kinesthetic.